Analisis Kegiatan Coping Stress Siswa SD Melalui Praktik Ice Breaking - Nurhaliza, Alya; Firdausi, Laily Amalia; Putri, Hellen Silvia Meilana; Sholihah, Ulya Dinatus; Zulfahmi, Muhammad Nofan (Tunas Nusantara, 2024)
Ice breaking is an effective strategy in helping elementary school students deal with stress. Through the analysis of stress coping activities, we can understand the positive impact of ice breaking practices in this context. Research shows that this method not only builds social connections among students, but also increases their engagement in learning. In observing the stress coping activities of elementary school students, the practice of ice breaking helps create a supportive environment. Students tend to feel more comfortable interacting with classmates after participating in this activity. This can reduce anxiety levels and increase their self-confidence. Apart from that, ice breaking can also act as a means to identify students’ talents and interests. By introducing a variety of activities, teachers can observe students’ responses to each activity. This opens up opportunities to direct students to extracurricular activities that match their interests, which can be a positive outlet for dealing with stress.Keywords : Ice Breaking, Students, Social